Extraordinary Women: (Harmony of Ibadah and Aqidah in Inventing the Perfection of Ramadan at the Salat Empat Puluh in Sijunjung) - Salma, Salma; Jarudin, Jarudin (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
The study aimed to analyze the activities and understandings of Muslim women in Sijunjung region accompanying the implementation of Ramadan fasting with salat empat puluh. The Salat empat puluh is the name/term of the activity because it is carried out for 40 (forty) days throughout Ramadan month and added 10 days before or after it. The data were obtained by observing the activity of salat empat puluh in 7 mosques/musallas/suraus in Sijunjung region during Ramadan in 2018 and also by interviewing several imams and women who were the members of the salat empat puluh. The qualitative data analysis was conducted descriptively through reducing, displaying and verification (drawing conclusions). The result of the study showed that the activity was dominantly done by women. These women were at menopause age but economically still very productive. During the days they worked in the fields, farms, and stalls, and in the evening they stayed in mosques or musallas to do salat in congregation, to substitute the congregational salat that were left behind, to read Qur`an, to study fiqh, Qur'an exegesis and to discuss the issues of tauhid. During those 40 days they never left salat in congregation, avoided immoral acts and really brought themselves closer (taqarrub) to Allah. When someone left the salat in congregation and did not replace it in the salat i'adah, then they considered that the salat empat puluh was invalid and no longer had the same value as those who completed it. In those 40 days these women showed the height of their faith and humanity quality in front of God.